A biorremediação do lauril éter sulfato de sódio presente em efluentes de indústrias cosméticas: uma revisão sistemática - Del’Labon, Giulia De Pinho (Universidade Federal de São Carlos, 2023)
With the growth of the personal hygiene and cosmetics market, the category's environmental concern requires actions to remedy the damage these products cause to the ecosystem. One of the concerns for water treatment plants is surfactants, with Sodium Lauryl Ether Sulfate (SLES) being one of the most used in the cosmetic industry worldwide. Studies on its bioremediation are indispensable for decision making and implementation of improvements in effluent recovery processes. This systematic review sought to evaluate the different biodegradation methodologies used in studies concerning the surfactant. Using the Google Scholar search engine and the Capes, Science Direct and Scopus databases, the articles were evaluated according to the OECD tests for immediate biodegradation and ISO 7875. Although the searches resulted in 11,016 articles, a low number of of works with relevance to the theme, where only 5 were selected for this systematic review. These 5 presented a low variety of conditions of pH, temperature and combination of microorganisms, which prevents a precise assessment of the biodegradation of Sodium Lauryl Ether Sulfate. To ensure assertive decisions about its removal in water treatment plants, further studies are needed to fill in the gaps found.
The bioremediation of sodium lauryl ether sulfate present in effluents from cosmetic industries: a systematic review
Keywords: Surfactantes aniônicos; SLES; Biorremediação; Anionic surfactants; Bioremediation; CIENCIAS BIOLOGICAS::MICROBIOLOGIA